Breakthrough Pain in Patients with Controlled or Uncontrolled Pain: An Observational Study. (2014) - Gatti, Antonio; Gentili, Marta; Baciarello, Marco; Lazzari, Marzia; Marzi, Rossella; Palombo, Elisa; Sabato, Alessandro F; Fanelli, Guido
Abstract : BACKGROUND: Breakthrough pain (BTP) is traditionally defined as a pain exacerbation in patients with chronic controlled pain. However, this definition has recently been challenged. OBJECTIVES: To evaluate the prevalence of unsatisfactory control in patients with chronic cancer pain, and investigate the frequency and intensity of BTP episodes. METHODS: A total of 665 patients with chronic cancer pain attending 21 pain therapy units in Italy were evaluated for baseline pain intensity and number of BTP episodes over a 30-day period. All patients started, continued or modified treatment for BTP at enrollment, according to medical judgment. RESULTS: The number of BTP events was higher in patients with uncontrolled baseline pain, although the intensity and duration of episodes were similar. In patients with uncontrolled baseline pain, the number of events decreased with time and reached values comparable with those reported in patients with controlled pain. Both the intensity of the pain and the duration of the BTP events exhibited similar values in the two groups at all time points, following increased monitoring and the prescription of analgesic medication. CONCLUSION: Patients with uncontrolled baseline pain experienced BTP flares with higher frequency, but similar intensity and duration with respect to patients with controlled pain at baseline. Notably, a close follow-up and adequate management of the BTP episodes led to an improvement of BTP in the observed patients.